PENERAPAN METODE MULTI SENSORI UNTUK MENINGKATKAN KEMAMPUAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 009 AIR EMAS - Edi Supadmi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
The background of this study is the lack of writing skills of students. This is due to: (a) instructional methods used by teachers always lectures, discussion and provision of duty; (b) students are not trained to write well and truly in the study; (c) the student is only assigned to write his own without the guidance of a teacher; and (d) interaction in the learning occurs only in one direction. To that end, researchers conducted research is conducted with the aim of improving students' writing skills by applying multi-sensory methods in classroom action research. This study was conducted in two cycles, data collection techniques used were observation activities of teachers and students, and a written test. Results of the study stated that through multi-sensory method of increasing students' writing ability. This is evidenced by: (a) the activities of teachers has increased in the first cycle to the second cycle. In the first cycle in the implementation of learning first meeting with a percentage of 45% after the second meeting with a percentage of 55%. Cycle II increased in all three meetings with the percentage of 70% and after the fourth meeting accomplished 75%. Besides the student activity also increased in the first cycle of the first meeting keatifan students reached 48% and in the second meeting reached 61%. In the second cycle to the 3rd meeting with the percentage of 71% and 4 meeting to reach 84%; and (b) the students' writing skills also increased in the first cycle in the implementation of learning first meeting with a percentage of 45% after the second meeting with a percentage of 55%. Cycle II increases at a meeting to 3 with a percentage of 70% and after the fourth meeting accomplished 75%.